Using the Storytelling Technique to Improve English Speaking Skills of Primary School Students - Fikriah Fikriah (English Education Journal, 2016)
This research was conducted to find out whether the use of Storytelling Technique (STT) could improve the English speaking skills of primary school students. This Classroom Action Research (CAR) project was done in two (2) cycles, where the procedures consisted of planning the action, implementing the action, observing and reflections. The instruments used for collecting the data were observation sheets for the teacher and students, and a speaking test and questionnaire for the students. The results showed that STT improved the speaking skills of the students’ especially in pronunciation fluency, accuracy, and comprehension of produced sentences. The data from the speaking tests showed that the mean score from the students after the first cycle was 5, and increased to 7 after the second cycle. It further showed that 58% of the students got scores above average in the first cycle and increased to 80% in the second cycle. From the observation sheet, the students’ participation gradually increased, with 55% in the first cycle and 86% after the second cycle.  Furthermore, based on the observation sheet from the teacher, the researcher also showed improvement in teaching where after the first cycle, she got a score of 61% which increased to 87% after the second cycle. Moreover, based on the responses to the questionnaire, 80% of the students responded positively to the implementation of the treatment. These results indicate that this classroom action research was a success where STT effectively improved the students’ English speaking skills.